2005
DOI: 10.1080/00365590500199855
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer with small-cell morphology: An immunophenotypic subdivision

Abstract: U-PC-SCM with a neuroendocrine immunophenotype is a histogenetically distinct entity with different clinical and laboratory manifestations which responds well to a cisplatin + etoposide CTH regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…These results are consistent with those published by Petraki et al , in which 86% of biopsies of SCC stained positively for synaptophysin and 71% for chromogranin A. [16] Other neuropeptides that may be synthesized by neuroendocrine cells and stain positive immunohistochemically include somatostain, alpha-human chorionic gonadotropin, and parathyroid hormone-related protein. [17] In differentiating small-cell prostate carcinoma from adenocarcinoma, TTF-1 and CD56 are also helpful markers.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those published by Petraki et al , in which 86% of biopsies of SCC stained positively for synaptophysin and 71% for chromogranin A. [16] Other neuropeptides that may be synthesized by neuroendocrine cells and stain positive immunohistochemically include somatostain, alpha-human chorionic gonadotropin, and parathyroid hormone-related protein. [17] In differentiating small-cell prostate carcinoma from adenocarcinoma, TTF-1 and CD56 are also helpful markers.…”
Section: Discussionsupporting
confidence: 92%
“…However, Papandreou et al . suggested that surgery could not be the proper treatment modality of SCCP due to the fact that most cases with SCCP have a distant metastasis at initial diagnosis [13]. Radiation therapy might be considered for local control of the disease with chemotherapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially modulated by a long list of factors, it can be considered as a universal regulator of NE phenotype. However, the proliferative activity of NE tumor cells of SCPC generally contrasts with that observed in adeno-PC even when assessment is performed at advanced stage (106). Although the proliferation rate of adeno-PC certainly increases in the metastatic setting, adeno-PC is still considered as a slow progressing tumor type (42), and it seems likely that tumor cells confined into NE-like clusters are likewise slow-growing or quiescent (Figure 1).…”
Section: Integrating Neuroendocrine Differentiation In the Context Ofmentioning
confidence: 99%